2023
DOI: 10.3389/fphys.2023.1129413
|View full text |Cite
|
Sign up to set email alerts
|

The eNAMPT/TLR4 inflammatory cascade drives the severity of intra-amniotic inflammation in pregnancy and predicts infant outcomes

Abstract: Introduction: Intra-amniotic inflammation (IAI) or chorioamnionitis is a common complication of pregnancy producing significant maternal morbidity/mortality, premature birth and neonatal risk of chronic lung diseases such as bronchopulmonary dysplasia (BPD). We examined eNAMPT (extracellular nicotinamide phosphoribosyltransferase), a critical inflammatory DAMP and TLR4 ligand, as a potential therapeutic target to reduce IAI severity and improve adverse fetal/neonatal outcomes.Methods: Blood/tissue samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…We have previously reported the effective use of the ALT-100 mAb in preclinical models of ARDS [51], radiation fibrosis [53], pulmonary hypertension [49,92], lupus vasculitis [54], NASH hepatic fibrosis and ischemia induced cardiac fibrosis [76], and chorioamnionitis [50]. Highly relevant to this study, in a preclinical pregnant mouse model of chorioamnionitis-related preterm birth (PTB), the ALT-100 mAb was shown to delay PTB, increase neonate survival, and reduce IAI-related PTB complications, including bronchopulmonary dysplasia and pulmonary hypertension [48].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We have previously reported the effective use of the ALT-100 mAb in preclinical models of ARDS [51], radiation fibrosis [53], pulmonary hypertension [49,92], lupus vasculitis [54], NASH hepatic fibrosis and ischemia induced cardiac fibrosis [76], and chorioamnionitis [50]. Highly relevant to this study, in a preclinical pregnant mouse model of chorioamnionitis-related preterm birth (PTB), the ALT-100 mAb was shown to delay PTB, increase neonate survival, and reduce IAI-related PTB complications, including bronchopulmonary dysplasia and pulmonary hypertension [48].…”
Section: Discussionmentioning
confidence: 94%
“…We previously used genomic strategies and identified extracellular nicotinamide phosphoribosyltransferase (eNAMPT) as a novel DAMP and TLR4 ligand that potently initiates NF-κB transcription-dependent inflammatory responses and cytokine release [47]. We have shown that the eNAMPT/TLR4 inflammatory cascade is a druggable pathway in preclinical models of pulmonary hypertension [48][49][50], acute respiratory distress syndrome [51], radiation-induced lung disease [52,53], lupus vasculitis [54], and Crohn's disease [55,56].…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB is a downstream signaling linked by TLR4. LPS could directly induce TLR4 and activation of NF-κB signaling, which in turn led to production of inflammatory factors [ 36 , 37 ]. Given the role of TLR4/NF-κB signaling pathway in inflammation, we investigated the beneficial effect of inhaled H 2 on LPS-induced BPD, and we raised the question: does hydrogen inhibit inflammation by downregulating the expression of the hub protein TLR4 and subsequently reducing the activity of the NF-κB-mediated inflammatory signaling pathway?…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptors (TLRs) are crucial protein molecules involved in the body’s nonspecific immune response, acting as a bridge between terms innate and adaptive immunity ( 41 ). Current research indicates that TLR4 can promote preterm birth by upregulating the expression of pro-inflammatory factors and chemokines ( 42 ). Studies have shown similarities in the changes of white blood cells between infection-induced preterm labor and non-infected full-term labor, which can be attributed to the direct or indirect effects of TLR4 ( 43 ).…”
Section: Discussionmentioning
confidence: 99%